Global dynamics of Shi'a marriages religion, gender, and belonging - Shanneik, Yafa ca. 20./21. Jh; Moors, Annelies 1953- (The politics of marriage and gender, 2022)
Muslim marriages have been the focus of considerable public debate in Europe and beyond, in Muslim-majority countries as well as in settings where Muslims are a minority. Most academic work has focused on how the majority Sunni Muslims conclude marriages. This volume, in contrast, focuses on Twelver Shi'a Muslims in Iran, Pakistan, Oman, Indonesia, Norway, and the Netherlands. The volume makes an original contribution to understanding the global dynamics of Shi'a marriage practices in a wide range of contexts--not only its geographical spread but also by providing a critical analysis of the socio-economic, religious, ethnic, and political discourses of each context. The book sheds light on new marriage forms presented through a bottom up approach focusing on the lived experiences of Shi'a Muslims negotiating a diverse range of relationships and forms of belonging